Evaluating the learning environment in Dental colleges from students’ perspective; a qualitative exploratory research - Orakzai, Gulmina Saeed; Gillani, Syeda Munazza; Irshad, Saima; MahRukh; Tiwana, Madeeha Nazar; Shaukat, Sidra (Journal of Rawalpindi Medical College, 2023)
Objective: Learning environment has a great role in students learning, achievement and success. It is also essential for the development of curriculum. The aim of this study is to document the perception of dental students regarding their learning environment. Material and methods: This qualitative research were conducted from Dec 2021 to May 2022, at four dental colleges of Rawalpindi. A total of 16 students from all these college who were regularly enrolled and voluntary participating in the study were included. Focus group interview (n=4 in each group) comprised of students from both basic sciences year (1st and 2nd year BDS) and clinical years (3rd and final year BDS). Data was transcribed verbatim and thematic analysis was done. Result: Students overall expressed a good level of satisfaction with the learning environment but pointed out some issue which were summed up under major themes identified such as issues in lectures, issues in clinical teaching, issue in the dental curriculum and lack of academic motivation. Conclusion: This study suggests that the dental students generally hold a positive perception towards their learning environment, but they pointed out the short comings in their lectures, clinical teaching, dental curriculum and dearth of motivation. Taking students view point regarding their learning environment will help the stake holders and policy makers to provide better learning environment with more facilities and support system for the students to enhance their learning.